2005
DOI: 10.1111/j.1442-2050.2005.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen years follow up of achalasia: a prospective study of graded dilatation using Rigiflex balloon

Abstract: Pneumatic balloon dilatation is the treatment of choice for esophageal achalasia. Rigiflex (Microvasive, Watertown, MA) polyethylene balloon dilators have been used with varying success and complications. The aim of this study was to evaluate the efficacy of graded balloon dilatation, to achieve symptomatic improvement in patients with achalasia. From January 1987 until the end of December 2003, 300 patients were evaluated and treated for achalasia, with 30 mm balloons. Patients who did not achieve satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
3
29
0
1
Order By: Relevance
“…A timed barium esophagram was performed as an objective assessment of improvement in esophageal emptying in all treated patients 2,8 . Before the examination, patients were asked to fast overnight prior to the test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A timed barium esophagram was performed as an objective assessment of improvement in esophageal emptying in all treated patients 2,8 . Before the examination, patients were asked to fast overnight prior to the test.…”
Section: Methodsmentioning
confidence: 99%
“…Pneumatic dilatation in patients with esophageal achalasia is generally considered to be the first‐choice procedure 1–3 . The effective disruption of circular muscle fibers of the lower esophageal sphincter (LES) is the theoretical basis for the benefits associated with balloon dilatation 2 . However, recently, retrievable, covered stent placement has been involved as a potential effective method to treat esophageal achalasia 4–7 .…”
Section: Introductionmentioning
confidence: 99%
“…The techniques used for pneumatic dilatation depend on the centre, with variations in the type of instruments, balloon size, timing of dilatation, and frequency of dilatation. Despite all of the possible permutations, estimates of the likelihood of success and complications are remarkably stable [6,10,14,24,31,32,37,39]. Therefore, for the purposes of this analysis we assumed that the method of dilatation was inconsequential, and pooled all methods to form the probability estimates.…”
Section: Decision Analytic Modelmentioning
confidence: 97%
“…Multiple large series and reviews show a perforation rate of <1-3%. 18,38,[51][52][53] It has been noted that the risk of perforation is greatest on the initial dilatation as opposed to subsequent dilatations. 52,53 Evaluation of predictive factors for perforation revealed that high distal oesophageal contraction amplitudes (>70 cm H 2 O) were more predominant in those with subsequent perforation.…”
mentioning
confidence: 99%